Manejo de paciente con periodontitis crónica en la clínica odontológica de la UDLA: reporte de caso. - Almeida Arboleda, Adriana Carolina (2017)
INTRODUCTION: Periodontal disease is one of the most common pathologies in the oral cavity, most patients who suffer from it do not focus on seeking a proper treatment in time. From a multifactorial etiology with a main trigger factor such as bacterial plaque, to the loss of teeths supporting tissues like the periodontal ligament and alveolar bone, periodontal disease damages the function, shape and aesthetic of the masticatory system since the consequences can lead to the irreversible loss of teeth. METHODS: In the present case report, phase one of periodontal therapy was performed, it included the removal of both bacterial plaque and calculus, elimination of over flow restorations as well as plaque retentive factors, education and motivation about a correct, appropriate and a frequently moderate dental brushing technique, use of dental floss as well as mouthwashes, finishing with a reassessment and comparation between gain or loss in probing depth according to the initial periodontogram and the re-evaluation. RESULT: Subsequent to non-surgical periodontal treatments phase one, statistically significant changes were found in the decrease of inflammation as well as in the measurements of probing depth after the re-evaluation corresponding to 4 weeks. RECOMMENDATION AND CONCLUSION: Periodontal treatment culminates with key elements, as well as a good patient education about oral care. The decision to re-scale certain areas where the disease has not fully given in, is taken, in order to maintain periodic controls between 3 or 4 months. It is recommended to focus in subjects like dental brushing, the use of dental floss and the use of mouthwashes.